Abraham — Knight of Faith or Counterfeit? Abraham Figures in Kierkegaard, Derrida, and Kafka - Butin, Gitte Wernaa (KIERKEGAARDIANA, 2000)
Abraham — Knight of Faith or Counterfeit? Abraham Figures in Kierkegaard, Derrida, and Kafka